General transcription factor IIIAa regulates the transcription of somatic 5S rRNA and influences embryonic organ development in zebrafish - Junzhi Luo; Binbin Tao; Ji Chen; Yanlong Song; Wei Hu (Marine Life Science & Technology, 2025)
Transcription factor IIIA (TFIIIA) is a zinc finger protein that facilitates the assembly of a transcription complex by recruiting transcription factors TFIIIB and TFIIIC, along with RNA polymerase III, to initiate the transcription of 5S rRNA genes. However, the effects of TFIIIA knockout in vertebrates remain unclear. To address this, we investigated the function of a homologous general transcription factor IIIAa, gtf3aa , identified as a maternal factor in zebrafish. During early embryonic development, gtf3aa expression initially increased and subsequently declined. At 12 h postfertilization, gtf3aa mRNA was detected at notably low levels in the embryo, whereas by three days postfertilization, its mRNA level gradually increased in the larvae. The gtf3aa was broadly expressed in various embryonic tissues of zebrafish, with higher expression levels observed in the brain, heart, liver, and muscle. Knockout of gtf3aa significantly suppressed somatic 5S rRNA transcription in early zebrafish embryos and larvae, resulting in a reduction in the number of mature monoribosomes and polyribosomes. The gtf3aa −/− larvae exhibited slow growth and delayed yolk absorption, along with impaired development of the eyes, heart, swim bladder, liver, and intestinal tissues. Additionally, expression of genes involved in metabolic signaling pathways, including the peroxisome proliferator-activated receptor pathway, was reduced. The gtf3aa −/− zebrafish did not survive beyond seven days postfertilization. This study offers preliminary insights into the role of gtf3aa in regulating somatic 5S rRNA transcription and embryonic organ development in zebrafish.